The Market Economy Discourse on Education: Interpretation, Impact, and Resistance - Hyslop-Margison, Emery J. (Alberta Journal of Educational Research, 2000)
This article suggests that the most serious threat posed to contemporary education is the deleterious impact that market economy policies have on current curriculum theory and development. It explores the market economy discourse on education that emerges internationally from the Organization for Economic Cooperation and Development (OECD), and domestically from private institutions such as the Conference Board of Canada (CBOC) and public ministries such as Industry Canada. These various organizations promote the market economy discourse on education by framing discussions on curriculum policy between government and business interests. By referring to the primary sources of the market economy discourse on education, then, this article draws attention to the global economic vision currently shaping Canadian schools and explores its impact on domestic education policy. Further, it proposes a means whereby those teachers holding a less intractable perspective on education might resist the current market economy siege on schools. Ironically, this approach involves using the critical tools appropriated by the market economy discourse on education in a manner entirely unintended and unforeseen by its supporters.